2004
DOI: 10.1002/qaj.288
|View full text |Cite
|
Sign up to set email alerts
|

Data quality of the clinical trial process – costly regulatory compliance at the expense of scientific proficiency

Abstract: The reasons for the belief in the need for perfection of clinical data are carefully nursed myths. The logical shortcomings in Good Clinical Practice are nothing but embarrassing to its scientifically trained promoters. Modern quality management methods, which increasingly degrade the importance of inspections, are described and their application in clinical research recommended. The documentation of procedures to attain acceptable quality levels of trial data is suggested to be standardized into a Quality Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…https://doi.org/10.1017/cts.2024.551 Published online by Cambridge University Press Non-quantitative evidence: A total of 12 non-quantitative articles were included, 9 opinions 23,32,[57][58][59][60][61][62][63] , and 3 reviews [26][27][28] Opinion: Two of the nine opinion papers reported a clinical trial quality event that served as a major inflection point in thinking and approach. 57,58 These articles reported NIH tightening the clinical trials monitoring requirements in response to the finding of fraud in the National Surgical Adjuvant Breast and Bowel Project (NSABP) study group.…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…https://doi.org/10.1017/cts.2024.551 Published online by Cambridge University Press Non-quantitative evidence: A total of 12 non-quantitative articles were included, 9 opinions 23,32,[57][58][59][60][61][62][63] , and 3 reviews [26][27][28] Opinion: Two of the nine opinion papers reported a clinical trial quality event that served as a major inflection point in thinking and approach. 57,58 These articles reported NIH tightening the clinical trials monitoring requirements in response to the finding of fraud in the National Surgical Adjuvant Breast and Bowel Project (NSABP) study group.…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…Lö rstad is one critic who questions the industry application of ICH GCP [2]. The criticism is mostly related to the over-interpretation of the ICH GCP guideline.…”
Section: Ich Gcp Criticismmentioning
confidence: 99%
“…It is a widespread misunderstanding that the quality in a clinical trial is dependant on the degree of 'errors' discovered. Many companies apply a perfectionist approach whether 'errors' are important or not for the outcome of a trial [2]. The present system focuses on doing 'things right' rather than doing the 'right things'.…”
Section: Ich Gcp Criticismmentioning
confidence: 99%
“…The authors' personal experience is that quality is sometimes perceived as something that is done in addition to and on top of day-to-day work or, at worst, something that is the responsibility of the quality assurance organization to secure at the end of a project. In 2004, Lörstad 15 wrote about data quality in the clinical trial process and pointed out that the Japanese mass production industry more than 50 years ago realized that their previous dependence on inspections was inefficient and costly. This insight spread quickly and got expressed in the term "you cannot inspect quality into a product," which is understood across the manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
“…For some reason, the term has not been embraced by pharmaceutical research and Lörstad foresees a risk that this part of the industry may soon be isolated in defending inspections as a superior means of quality assurance. 15 Ten years later, Power 11 cited the European Pharmacovigilance regulations 2 and the Medicines and Healthcare Products Regulatory Agency (MHRA) Guideline for Good Clinical Practice for Clinical Trials 16 to illustrate that the focus within pharmaceutical research is still on compliance confirmed by inspections 11 which indicates that Lörstad's 15 prediction from 2004 is still relevant.…”
Section: Introductionmentioning
confidence: 99%